Quartz crystal microbalance as a tool for kinetic enzymatic assays by variation of pH - dos Santos, Fernanda Cesar [UNESP]; Goncalves, Luis Moreira; Riccardi, Carla dos Santos [UNESP]; Barros, Aquiles Araujo; Bueno, Paulo Roberto [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
In this work, it is shown that the quartz crystal microbalance (QCM) can be a powerful and simple tool for quick and precise kinetic enzymatic assays. This is shown by measuring immobilized acetylcholinesterase (AChE) activity with variations of pH as a case study. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Quartz crystal microbalance; Acetylcholinesterase (AChE); Kinetic enzymatic assays